Determinants Of Personal Financial Management: Exploring The Mediating Role of Locus of Control Among Multigenerational Caregivers in Medan - Wahyuni, Sri Fitri; Sari, Maya; Astuty, Widia; Puji Lestari, Sri; Rifki Hafas, Hafriz (Journal of International Conference Proceedings, 2025)
This study investigates the impact of financial literacy, individual spiritual intelligence, peer group, and love of money on personal financial management among the multigenerational caregivers (sandwich generation) in Medan City, with locus of control serving as a mediating factor. Utilizing a quantitative, associative research design, data were gathered from 96 respondents via structured questionnaires and analyzed using Partial Least Squares (PLS). The analysis reveals that both financial literacy and individual spiritual intelligence significantly enhance personal financial management and contribute to a stronger locus of control. Although the peer group exerts a significant influence on locus of control, its direct impact on personal financial management is not statistically significant. In contrast, love of money demonstrates a significant positive effect on personal financial management, while its effect on locus of control remains insignificant. Furthermore, locus of control significantly improves personal financial management and mediates the relationships between the independent variables and financial management practices. The findings underscore the potential of targeted financial education, initiatives to bolster spiritual intelligence, and the cultivation of supportive peer networks to enhance financial management among the sandwich generation.